Estimation of perinatal mortality rate for institutional births in Rajasthan state, India, using capture–recapture technique - Mony, Prem K (BMJ Open, 2015)
OBJECTIVE: The objective of our investigation was to estimate the perinatal mortality rate among institutional births and to compare the sensitivities of different data collection methods. SETTING: A hospital-based prospective cohort study was undertaken during late-2012 in 21 public sector health facilities of 10 districts of the northern state of Rajasthan, India. PARTICIPANTS: A total of 6872 births were included in this epidemiological study. PRIMARY AND SECONDARY OUTCOME MEASURES: Perinatal mortality rate of institutional births was the primary outcome. Sensitivities of ‘active’ and passive’ data collection methods were the secondary outcome measures. METHODS: All stillbirth data were from routine government records (‘passive system’); early neonatal outcome data from government records (‘passive’) were compared against the method of ‘phone-tracking’ of outcomes through the community health worker (‘active system’). The Lincoln-Petersen formula for capture-recapture method was used to calculate the probable missing number of early neonatal deaths and thereby estimate the institutional perinatal mortality rate. RESULTS: Ratio of births in district:subdistrict facilities was 55:45. The estimated perinatal mortality rate (95% CI) by capture–recapture method was 35.8 (34 to 37) per 1000 births. The sensitivity of the passive system was 87–89% while the sensitivity of the active system was 91%. Three-fourths of perinatal deaths were documented as stillbirths. However, for these reported intrauterine deaths or stillbirths, clinical classification by typologies (term vs preterm; intrapartum vs antepartum; macerated vs fresh; with or without congenital anomalies) was absent in the recording system. CONCLUSIONS: Capture–recapture technique can be used to estimate the institutional perinatal mortality rate and also to assess the level of under-reporting by the ‘passive’ government reporting system. This can subsequently be used for monitoring of trends and studying the impact of health interventions. Accurate clinical categorisation of perinatal deaths is also recommended for improving quality of care.